Advances in multi-photon processes and spectroscopy Volume 23 - Lin, S. H.; Villaeys, A.A.; Fujimura, Y. (Singapore : World Scientific Publishing Co. Pte Ltd., 2016)
'This volume presents recent progress and perspectives in multi-photon processes and spectroscopy of atoms, ions, and molecules. The subjects in the series cover the experimental and theoretical investigations in interdisciplinary research fields in natural science including chemistry, physics, bioscience and material science.'--Publisher's website.
Title from PDF file title page (viewed September 29, 2016).
Includes bibliographical references.
Electronic reproduction.
Mode of access: World Wide Web.
Keywords: Multiphoton processes; Electronic books